Neue Erkenntnisse über die Auswirkungen der Ozeanversauerung auf marine Lebensgemeinschaften - Bach, Lennart T.; Riebesell, Ulf (Wissenschaftliche Auswertungen, 2016)
New insights into the impact of oceanic acidification on marine life communities: The pelagic realm is the largest interconnected ecosystem on our planet. It is inhabited by an enormous diversity of organisms, ranging from microscopic plankton to huge baleen whales. All these organisms interact either directly or indirectly with each other in a complex food-web. The stability of the food-web is currently challenged by major anthropogenic perturbations. Among these perturbations is ocean acidification – the absorption of anthropogenic CO2 which reacts with seawater and causes a profound decline in seawater pH. New studies with natural plankton communities show that ocean acidification can re-structure marine food-webs and modify elemental cycles with possible consequences for ecosystem services on which humans depend.